Pendampingan Pokdarwis dalam Pembuatan Paket Wisata Konservasi Pulau Tidung Kepulauan Seribu Jakarta - Hafidz, Aisha Mutiara; Hakim, Fahmi Salman; Hasan, Rinie Octaviany (Yayasan Pendidikan Mitra Mandiri Aceh(YPMMA), 2025)
Indonesia as an archipelago has the highest marine biodiversity in the world. One area that holds tremendous potential is Tidung Island, South Thousand Islands. However, its marine ecosystem faces various threats due to low public environmental awareness and the lack of capacity of local groups in managing conservation-based tourism. This service activity aims to assist the Tidung Island Tourism Awareness Group (Pokdarwis) in designing conservation tourism packages based on community participation and environmental sustainability. This community service was carried out from April 8-30, 2025 offline at the Tidung Island Tourism Village. The implementation method includes Focus Group Discussion (FGD), observation and interview, as well as socialization and training. The results showed that Pokdarwis has high enthusiasm in developing conservation tourism, but still faces challenges in terms of conservation knowledge, tour package preparation, and promotion. The mentoring activities provided improved understanding and technical skills for Pokdarwis in designing conservation-based tourism products, which are aligned with the principles of special interest tourism and regenerative tourism. The hope is that through collaboration between local communities and supporting parties, Tidung Island will be able to develop tourism that is not only economically attractive but also contributes to the preservation of marine ecosystems and the empowerment of local communities in a sustainable manner